When preservice and inservice teachers join forces: A collaborative way to support the enactment of new coding curricula in mathematics classrooms - Laura Broley; Chantal Buteau; Jessica Sardella (Journal of Pedagogical Research, 2023)
The importance of computational thinking skills in mathematics has been recognized in educational research for a long time. More recently, this recognition has materialized in formal international recommendations (e.g., by PISA's 2022 Mathematics Framework) and in national or provincial curricular reforms (e.g., in France, Sweden, and Canada) that promote the incorporation of coding in mathematics classrooms. This has led to opportunities as well as challenges for mathematics teachers, and a pressing need for work on teacher training. To contribute to this emerging area, we report on a professional development experience in which 25 inservice teachers collaborated with 36 preservice teachers to plan, implement, and reflect on the implementation of coding-based mathematics activities (using Scratch or Python) with Gr. 5-9 school students. Teachers' reflections are shared as insights gained through the experience, which may be of interest to other teachers or policy makers engaged in the implementation of coding in school subjects such as mathematics. With other researchers and teacher educators in mind, participating teachers' reflections are also used as a springboard to evaluate the reported training approach, discuss the approach in the context of existing literature, and provide some perspectives for the future.